THE THEORETICAL FOUNDATIONS OF COGNITIVE TECHNOLOGIES AND PEDAGOGICAL DESIGN IN MUSIC EDUCATION - Tolibjanova Ikboloy Tokhirjon kizi (Modern American Journals, 2025)
This article explores the importance of implementing innovative pedagogical technologies in modern music education and highlights practical methods of their application. It examines the unique characteristics of music education, the concept of the competency-based approach, and its impact on musical development. The article also discusses problem-based learning, project-based instruction, cooperative teaching, and the contribution of information and communication technologies (ICT) to the educational process. The use of interactive methods and digital tools in music lessons, as well as innovations in the assessment system, are addressed in detail. The article presents practical recommendations for making music education more effective, engaging, and modern.
Keywords: Music education, innovative technologies, pedagogical approach, competence, modern methods, digital technologies, interactive methods, assessment system.